Screening of FDA-Approved Drug Library Identifies Adefovir Dipivoxil as Highly Potent Inhibitor of T Cell Proliferation - Voss, Linda; Guttek, Karina; Reddig, Annika; Reinhold, Annegret; Voss, Martin; Schraven, Burkhart; Reinhold, Dirk (Frontiers in Immunology, 2021)
Repositioning of approved drugs for identifying new therapeutic purposes is an alternative, time and cost saving strategy to classical drug development. Here, we screened a library of 786 FDA-approved drugs to find compounds, which can potentially be repurposed for treatment of T cell-mediated autoimmune diseases. Investigating the effect of these diverse substances on mitogen-stimulated proliferation of both, freshly stimulated and pre-activated (48 h) peripheral blood mononuclear cells (PBMCs), we discovered Adefovir Dipivoxil (ADV) as very potent compound, which inhibits T cell proliferation in a nanomolar range. We further analyzed the influence of ADV on proliferation, activation, cytokine production, viability and apoptosis of freshly stimulated as well as pre-activated human T cells stimulated with anti-CD3/CD28 antibodies. We observed that ADV was capable of suppressing the proliferation in both T cell stimulation systems in a dose-dependent manner (50% inhibition [IC50]: 63.12 and 364.8 nM for freshly stimulated T cells and pre-activated T cells, respectively). Moreover, the drug impaired T cell activation and inhibited Th1 (IFN-γ), Th2 (IL-5), and Th17 (IL-17) cytokine production dose-dependently. Furthermore, ADV treatment induced DNA double-strand breaks (γH2AX foci expression), which led to an increase of p53-phospho-Ser15 expression. In response to DNA damage p21 and PUMA are transactivated by p53. Subsequently, this caused cell cycle arrest at G0/G1 phase and activation of the intrinsic apoptosis pathway. Our results indicate that ADV could be a new potential candidate for treatment of T cell-mediated autoimmune diseases. Prospective studies should be performed to verify this possible therapeutic application of ADV for such disorders.